Rsa Security's Official Guide to Cryptography - Burnett Steve (Mcgraw Hill, 2004)
Want to keep your Web site safe? Learn how to implement cryptography, the most secure form of data encryption. Highly accessible, and packed with detailed case studies, this practical guide is written in conjunction with RSA Security--the most trusted name in e-security(tm). Part of the RSA Press Series. --This text refers to an out of print or unavailable edition of this title.